Desempenho de genótipos de arroz irrigado quanto ao frio na germinação e na emergência - Freitas, Demócrito Amorim Chiesa (2009)
The need to widen the seeding window of irrigated rice cultivars capable of germinating and producing normal seedlings under low soil temperatures led to the execution of this work, at the laboratory of the Plant Science Department from the Faculty of Agronomy Eliseu Maciel , Federal University of Pelotas and greenhouses at Embrapa s Temperate Climate (CPACT - Pelotas/RS) and Rice & Bean (CNPAF - Goiânia/GO) Experimental Stations. The experimental work focused on the identification of irrigated rice genotypes from an F2 generation tolerant to low soil temperatures at the germination and emergence stages, through the selection of cDNA fragments differentially expressed as the result to low temperature exposure during the germination phase. The procedure consisted of three stages; First stage involved selection, through physiological traits associated to genotype tolerance and sensitivity to germination onset and emergence under low temperature, among the 104 genotypes tested. The Second stage focused on the screening for variability for low temperature tolerance trait among the F2 progeny of a dialellic set of crossings, while the Third stage related to differentially expressed cDNA fragment selection, among embryos from low temperature tolerant and sensitive genotypes. Main results are as follows; a) A large variability for traits expressing tolerance to germination and emergence under low temperatures was determined among the genotypes tested, with BRS Atalanta, LTB 06002, LTB 06012 and LTB 06020 genotypes exhibiting superior germination values, whereas genotypes LTB 06014, Nourim Mochi and Oro exhibited higher emergence values. b) The rice genotypes with high germination values under low temperature conditions did not show the same trend during the emergence stage. c) The cDNA/AFLP technique proved effective in producing and identifying rice gene fragments differentially expressed, under ambient conditions of low temperature during germination. d) Four polymorphic fragments were identified for genotype BRS Firmeza at a temperature of 13°C, thus indicating that four genes were expressed under this condition.